Signaling mechanisms in mammalian sperm motility - Freitas, Maria João (2020)
The goal of sperm is to fertilize the oocyte. To achieve that purpose, it must acquire motility in the epididymis and hyperactivated motility in the female reproductive tract. Motility is only achieved when the sperm presents a fully functional flagellum, is capable of producing energy to fuel the movement, and suffers epididymal maturation and capacitation. Since sperm is a transcriptionally silent cell, motility depends on the activation and/or inhibitions of key signaling pathways. This review describes and discusses the main signaling pathways involved in primary and hyperactivated motility, as well as the bioenergetic mechanisms necessary to produce energy to fuel sperm motility. Although the complete human sperm motility process is far from being fully known, we believe that in the upcoming decades extensive progress will be made. Understanding the signaling pathways behind sperm motility can help pinpoint the cause of male infertility and uncover targets for male contraception.